Understanding the Challenges Facing Social Enterprise Sustainability - Guleid, Abdirahman Hussein (KASEM BUNDIT JOURNAL, 2014)
This article seeks to create a basic understanding of social enterprises, outlines how they operate, identifies some of its examples, determines various benefits that can be obtained from a social enterprise, identifies various skills required to run it, with an intention of identifying the possible challenges that can affect their operations and various managerial skills required to illustrate how social managers can optimize or make use of these factors to attain sustainability within a social enterprise. It later on develops a conceptual framework to indicate how these various factors that challenge the functioning of a social enterprise are interrelated and their effects on social enterprise sustainability. บทความฉบับนี้ เป็นความพยายามในการทำความเข้าใจเบื้องต้นเกี่ยวกับองค์กรธุรกิจสังคม โดยได้บรรยายถึงการดำเนินกิจการ ระบุตัวอย่างกิจการ ประโยชน์ที่ได้รับจากองค์กรธุรกิจสังคม คุณสมบัติที่จำเป็นในการดำเนินกิจการ ปัญหาและอุปสรรคในการดำเนินการ รวมทั้งทักษะในการบริหารที่ผู้บริหารกิจการจะต้องมีเพื่อให้ในการบริหารเกิดความยั่งยืนในองค์กรธุรกิจสังคม บทความนี้พัฒนากรอบแนวคิดที่แสดงว่าปัจจัยต่าง ๆ ที่ท้าทายการดำเนินกิจการขององค์กรธุรกิจสังคมนั้นมีความสัมพันธ์กันและมีผลกระทบต่อการบริหารองค์กรธุรกิจสังคมอย่างยั่งยืน